Experimental and numerical investigation of blade resonance in a centrifugal compressor for varying gas properties - Degendorfer Carsten (Journal of the Global Power and Propulsion Society, 2018)
The blades of centrifugal compressors are exposed to unsteady forces during operation which can result in resonance response conditions and failures due to high cycle fatigue. A typical source of excitation is the unsteady fluid structure interaction between the impeller blades and the downstream vaned diffuser. Centrifugal compressors are operated with various working fluids with a wide range of applications in the power and process industry. Understanding the excitation mechanisms for different working fluids will help to design aerodynamically efficient compressors, while ensuring mechanical integrity and reducing the number of experimental design validations. A variation in working fluid properties allows investigation of the contribution of blade forcing and damping while the modal response remains unchanged. Experiments have been conducted at ETH Zurich’s radial compressor facility with a state of the art industrial compressor design. Dynamic strain gauge measurements on the impeller blades were used to determine the amplitude response, damping properties and forcing at a defined resonance condition. Two working fluids have been investigated to vary compressor flow settings while the modal response remains unchanged. Unsteady flow simulations and harmonic FSI simulations were used to complement the experiments and to investigate the local blade forcing distribution, which then were linked to flow effects. Experiments showed a change in resonance amplitude up to a factor of 4 due to a change in the applied working fluid. Estimation of the damping ratio with a single degree of freedom model found the exciting force to be the main contributor to the differences in resonant response. The unsteady flow simulations were able to identify the locations on the blade surface which are responsible for the change in forcing. It was found that the forcing depends on wave propagation effects in the flow channel and on how the pressure field matches the mode shape.